A rapid and sensitive LC–MS/MS method for quantification of quercetin‐3‐O‐β‐d‐glucopyranosyl‐7‐O‐β‐d‐gentiobioside in plasma and its application to a pharmacokinetic study. (23rd February 2016) - He, Xin; Tao, Guizhou; Gao, Hang; Li, Keyan; Zhang, Yazhuo; Sun, Limin; Zhang, Yingjie
Abstract: A rapid and sensitive LC–MS/MS method with good accuracy and precision was developed and validated for the pharmacokinetic study of quercetin‐3‐ O‐β ‐d ‐glucopyranosyl‐7‐ O‐β ‐d ‐gentiobioside (QGG) in Sprague–Dawley rats. Plasma samples were simply precipitated by methanol and then analyzed by LC–MS/MS. A Venusil® ASB C18 column (2.1 × 50 mm, i.d. 5 μm) was used for separation, with methanol–water (50:50, v /v) as the mobile phase at a flow rate of 300 μL/min. The optimized mass transition ion‐pairs ( m / z ) for quantitation were 787.3/301.3 for QGG, and 725.3/293.3 for internal standard. The linear range was 7.32–1830 ng/mL with an average correlation coefficient of 0.9992, and the limit of quantification was 7.32 ng/mL. The intra‐ and inter‐day precision and accuracy were less than ±15%. At low, medium and high quality control concentrations, the recovery and matrix effect of the analyte and IS were in the range of 89.06–92.43 and 88.58–97.62%, respectively. The method was applied for the pharmacokinetic study of QGG in Sprague–Dawley rats. Copyright © 2016 John Wiley & Sons, Ltd.